"Let me tell you what we already know": Collective memory between culture and interaction. (August 2022) - Van de Putte, Thomas
This article presents the results of a qualitative micro-study of a 3-minute conversation between a research participant and a researcher. The talk in the interaction concerns the past of the contemporary Polish town of Oświęcim, internationally better known as Auschwitz. Borrowing methods and concepts from interactional sociology and linguistic ethnography, the article demonstrates that people know different cultural narratives about the same past event and are able to move between those narratives when the interactional context requires them to. The combination of micro-discourse analysis with ethnographic detail provides an insight in the entanglement of general cultural meanings and specific interactional dynamics when people attribute meaning to the past. The findings and methodological framework presented in this article also engage in a dialogue with some fundamental critiques on the field of memory studies. These include, among others, the need to connect the micro, meso, and macro, and the individual with the social, and the urge to actively develop and think through methods in memory studies research.